Perancangan Website untuk Menentukan Produk Paling Banyak Terjual di Bengkel Man Motor Metode TOPSIS - Vienne Anggelica Kurnia; Aldo Erianda; Dwiny Meidelfi (ULTIMA InfoSys, 2020)
Decision support system, or DSS, is a system to support decision making process. One commonly used method is TOPSIS. It is a method for decision making on multi-criteria issues, and is one of the simplest and easiest to understand. One of the functions of TOPSIS is to determine the most sold products. It requires a programming language called PHP to implement it on Website. PHP is a server-side programming language, so, all processes are conducted on server, then given to customers. Further, it requires a database for storing the data and software to manage the database is MySQL.